Analysis of the use of social media components on Serbian hotels’ websites - Ćamilović, Dragana (Naše gospodarstvo, 2025)
The research presented in this paper aims to determine to what extent hotels in Serbia use social media components on their websites. A total of 378 hotel websites in the Republic of Serbia were analysed. For each analysed hotel, the following attributes were observed: region, category, type, and size of the establishment, while the presence of valid links to social networks, the presence of a blog, Google Map, or a link to it, and the number of versions of the site in a foreign language were analysed on their websites. Descriptive statistics and the chisquare test were applied in data processing. The research has shown that hotels in Serbia insufficiently use social media components on their websites. These findings can be useful for hotels as they may indicate ways to improve their websites.
Keywords: analiza spletne strani; družabna omrežja; hotel website; hoteli; hotels; Serbia; social media; spletna stran hotela; Srbija; website analysis